A Young Poet from the Pavlodar Region: The Originality of the Poetry of Ilya Argentum - Novoselova, Elena; Iost, Olga (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2021)
The article is devoted to the study of poetry of Ilya Argentum, a Russian-speaking author of the Pavlodar region in Kazakhstan. The article presents an attempt to identify traits that characterise the creative output of this contemporary author. In the analysis, special attention is paid to how the worldview provides foundations for Argentum’s writing. When addressing issues such as the meaning of life, the true and false values, death and immortality, love, the role of the poet in modern life, the role his hometown has played in his own destiny, the young poet undoubtedly proves his individuality, both artistically and in terms of worldview. The poet’s significant creative potential and his original manner of writing help legitimizing the claim about the strengthening of the position of the local literature of the Pavlodar region in the contemporary literary process.